2003
DOI: 10.4049/jimmunol.170.3.1416
|View full text |Cite
|
Sign up to set email alerts
|

A Simian Replication-Defective Adenoviral Recombinant Vaccine to HIV-1 Gag

Abstract: In animal models, E1-deleted human adenoviral recombinants of the serotype 5 (AdHu5) have shown high efficacy as vaccine carriers for different Ags including those of HIV-1. Humans are infected by common serotypes of human adenovirus such as AdHu5 early in life and a significant percentage has high levels of neutralizing Abs to these serotypes, which will very likely impair the efficacy of recombinant vaccines based on the homologous virus. To circumvent this problem, a novel replication-defective adenoviral v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
185
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(195 citation statements)
references
References 27 publications
9
185
1
Order By: Relevance
“…Finally, it has been reported that injection of Ad vectors is likely to induce neutralizing antibodies to the virus, thereby hampering its immunogenic efficiency. 46,47 Indeed, we have detected high titers of Ad neutralizing antibodies in the transgenic mice after Ad injection that have a detrimental effect on the immunogenicity of subsequent Ad injections. However, unlike Ad, plasmid DNA injection can fully boost the T-cell response elicited by Ad injection (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…Finally, it has been reported that injection of Ad vectors is likely to induce neutralizing antibodies to the virus, thereby hampering its immunogenic efficiency. 46,47 Indeed, we have detected high titers of Ad neutralizing antibodies in the transgenic mice after Ad injection that have a detrimental effect on the immunogenicity of subsequent Ad injections. However, unlike Ad, plasmid DNA injection can fully boost the T-cell response elicited by Ad injection (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…Chimpanzee adenoviral vectors have been shown to elicit strong CD8 + T cell responses to transgene products [13]; however, it is unknown whether oral vaccination with these vectors induces mucosal CD8 + T cells including in animals with pre-existing immunity to a common human adenovirus serotype. Here we tested the intestinal mucosal responses to oral and intramuscular (i.m.)…”
Section: Introductionmentioning
confidence: 99%
“…While attenuation of IgA responses was eventually observed, the ability to immunize multiple times appears effective as a priming regimen for other vaccines or for the use of other serotypes of Ad [59][60][61][62]. Proof of principle is demonstrated here where mucosal oral priming of macaques by oral Ad administration was followed by mucosal boosting with an intranasal peptide vaccine.…”
Section: Discussionmentioning
confidence: 91%